Technology and application of treating water inrush disasters in underground engineering with the method of physical detection combined with grouting - Jiang, Huangbin; Jiang, Chu; Chen, Di; Qiu, Xiang (Frontiers in Earth Science, 2025)
The water gushing disaster in karst unfavorable geology has always been one of the difficult problems to be solved in the engineering field. In view of engineering problems such as water gushing in karst geology with relatively high-water flow velocity and water seepage at the joints of the underground diaphragm wall which is concealed, a treatment method for water gushing disasters in karst geology based on physical detection combined with grouting is proposed. The main steps of this method are as follows: Firstly, according to the analysis results of engineering geological investigations, by selecting appropriate physical detection means, accurately locate the hidden danger positions such as underground water gushing channels and cracks. Then, based on the results of physical detection, select appropriate grouting materials and techniques to conduct water blocking treatment at the water gushing points and effectively block the water gushing paths. In addition, the feasibility of the above method has also been verified through engineering applications. For the water gushing problem in the limestone area with extensive karst development, the electrical method of geophysical exploration technology was adopted to clarify the karst water gushing channels. And combined with the clay-cement paste grouting blocking technology to block them. The results show that the water blocking effect is obvious, and the water gushing volume has been drastically reduced from 103,900 to 8,600 m³/d, with a reduction rate as high as 91.72%. Moreover, for the concealed water gushing disasters at the joints of the underground diaphragm wall, the sonar detection method was selected to explore the positions of water gushing. Then the cement-water glass double-liquid grouting method was used to conduct anti-seepage treatment at the water gushing positions. An inspection of the water gushing situation after treatment found that the leakage phenomenon at the joints was significantly reduced. The research results can provide certain references for the design of treatment schemes for similar water gushing disasters in karst unfavorable geology.